2011
DOI: 10.1111/j.1365-2788.2011.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

The extent and nature of need for mealtime support among adults with intellectual disabilities

Abstract: These findings not only highlight the need for a multidisciplinary approach to mealtime interventions (paying particular attention to psychological and environmental as well as physical issues), but also signal the daily difficulties faced by carers and paid support workers providing such support and illustrate their potentially crucial role in managing the serious health risks associated with eating and drinking difficulties in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
2
44
1
2
Order By: Relevance
“…Research has also found that individuals with dementiaassociated dysphagia of Down syndrome and those with more severely involved cerebral palsy with limited mobility required more assistance at mealtimes. 37,38 RDNs should work with speech language pathologists and occupational therapists to include details such as texture modifications, pacing, encouragement, positioning, and behavior modifications in the feeding plan of care and work with caregivers to ensure and reinforce understanding. (continued on next page) …”
Section: Mealtime Assistancementioning
confidence: 99%
“…Research has also found that individuals with dementiaassociated dysphagia of Down syndrome and those with more severely involved cerebral palsy with limited mobility required more assistance at mealtimes. 37,38 RDNs should work with speech language pathologists and occupational therapists to include details such as texture modifications, pacing, encouragement, positioning, and behavior modifications in the feeding plan of care and work with caregivers to ensure and reinforce understanding. (continued on next page) …”
Section: Mealtime Assistancementioning
confidence: 99%
“…The biennial New South Wales (NSW) Ombudsman (2013) reports on the circumstances surrounding deaths of adults with disabilities in care highlight continuous failures in the system to protect people with disabilities from dysphagiarelated safety incidents (NSW Ombudsman, 2013). Ball et al (2012) estimated that 15% of all adults with severe intellectual disabilities required support for all eating-related activities. Unfortunately, one third of people with a disability, particularly those with high support needs, report that they do not receive the assistance that they need for core activity limitations, including eating and drinking recommendations (Australian Bureau of Statistics, 2013).…”
Section: Dysphagia-related Safety Incidents and Patient Safety Framewmentioning
confidence: 99%
“…Such dysphagia-related safety incidents are expensive to governments and disability organisations (Access Economics, 2008). Additionally, they are distressing to the person with dysphagia (Balandin, Hemsley, Hanley, & Sheppard, 2009) and those who provide care and support (Ball et al, 2012).…”
Section: Dysphagia-related Safety Incidents and Patient Safety Framewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, hasta la fecha, la estimación del estado de hidratación en personas con DI no ha recibido atención en la literatura científica a pesar de tener un mayor riesgo de deshidratación (Ball et al 2012;Lazenby, 2008). Esta situación podría ser incluso más complicada en hombres que en mujeres, dado que las mujeres poseen un umbral termorregulador superior y, por lo tanto, no empiezan a sudar hasta que la temperatura central es mayor (López et al 1994).…”
Section: Introductionunclassified